Revising rates of asymptomatic Zika virus infection based on sentinel surveillance data from French Overseas Territories. (December 2017) - Subissi, Lorenzo; Daudens-Vaysse, Elise; Cassadou, Sylvie; Ledrans, Martine; Bompard, Priscillia; Gustave, Joël; Aubry, Maité; Cao-Lormeau, Van-Mai; Mallet, Henri-Pierre
Highlights: Asymptomatic Zika virus infections have been overestimated. Surveillance data confirm the results from seroprevalence studies. The use of easy-to-implement surveys to estimate ZIKV circulation during outbreaks is proposed. Abstract: French Polynesia and the French Territories of the Americas (FTAs) have experienced outbreaks of Zika virus (ZIKV) infection. These territories used similar sentinel syndromic surveillance to follow the epidemics. However, the surveillance system only takes into account consulting patients diagnosed with ZIKV disease, while non-consulting cases, as well as asymptomatic cases, are not taken into account. In the French territories under study, the ratio of consulting to non-consulting patients was found to likely be as low as 1/3 to 1/4, and rough estimates of the ZIKV asymptomatic infections indicated a lower rate than previously reported (i.e., not more than half).